Le Boogie Woogie: Inside an After-Hours Club - Williams, Terry M. (The Cosmopolitan Life, 2020)
Frontmatter -- CONTENTS -- PREFACE -- INTRODUCTION -- 1. THE SETTING -- 2. THE SCENE -- 3. THE CHARACTERS -- 4. AFTER- HOURS NOW -- CONCLUSION. A Culture of Refusal -- ACKNOWLEDGMENTS -- Appendix 1. METHODOLOGICAL APPENDIX -- Appendix 2. FIELD NOTE SAMPLES -- Appendix 3. WHERE ARE THEY NOW? -- GLOSSARY -- NOTES -- BIBLIOGRAPHY -- INDEX